Bancassurance-An Emerging Trend in Indian Service Sector - Neelamegan, R.; Pushpa Veni, K. (Indian Journal of Marketing, 2009)
With the globalization and liberalization, the service sector has been witnessing a lot of changes. Life insurance companies require immense distribution strength and tremendous manpower to reach out to such a huge customer base. This distribution will undergo a sea change as various insurance companies are proposing to bring insurance products into the lives of the common man by making them available at the most basic financial point, the local bank branch, through Banc assurance. This paper aims to assert the concept, "Banc assurance"-a term coined by combining the two words bank and insurance (in French)-connotes distribution of insurance products through banking channels. Banks, with their geographical spread and penetration in terms of customer reach of all segments, have emerged as viable sources for the distribution of insurance products. In India, as elsewhere, banks are seeing margins decline sharply in their core lending business. Consequently, banks are looking at other avenues, including the sale of insurance products, to augment their income. The sale of insurance products can earn banks very significant commissions. However, the evolution of bancassurance as a concept and its practical implementation in various parts of the world, have thrown up a number of opportunities and challenges. Hence, there is a need to analyze the strength, weakness, opportunities and threats (SWOT Analysis) in the context of bancassurance experiment in India.